Comparative evaluation of JSY services at different health care settings of Rewa, Madhya Pradesh - Trivedi, Rohit; Adhikari, Paharam; Singh, Sandeep; sharma, Vivek; Nath, Som (Indian Journal of Community Health, 2014)
Introduction: JSY is a safe motherhood intervention and modified alternative of the National Maternity Benefit Scheme (NMBS).It was launched on 12th April 2005 by the Honorable Prime Minister. JSY has been implemented in all states and UTs with special focus on low performing states under the National Rural Health Mission (NRHM) with objective to reduce maternal, neo-natal mortality and promote institutional delivery among pregnant women of rural and urban areas and it is integrated with cash monetary help to pregnant women. Objective: To evaluate antenatal and post natal care services provided under JSY at different health care settings & to know the client suggestions for improvement in JSY. Methodology: this is a health care institute based observational cross sectional study including randomly selected 200 JSY beneficiary mothers from the different health care settings i.e. PHC,CHC,DH & Medical College Hospital; of Rewa Distt, M.P. Data was collected with the help of set proforma & then analyzed with applying epi info 2000.Chi square test was applied appropriately. Results: in case of ANC services provided at different health care settings it was observed that services were provided among more numbers of mothers at higher centers in comparison of PHC & CHC. The distribution of ANC provided to the beneficiary mothers among different health care settings was found to be statistically significant (X2 =17.24, p=0.002), similarly postnatal services were also provided among more numbers of mothers at Higher centers. 120 (60%) mothers suggested that there should be provision of other services i.e. Diet, tonics, and medicines during or after hospital stay along with cash benefit for better utilization of JSY.